The architecture of organizations as missed opportunity in political research - Marian Döhler (Public Administration, 2020)
Few scholars in political science or public administration deny that organization matters. However, the rare application of an organizational perspective in research suggests otherwise. To revive the awareness of organizations as unit or level of analysis, attributed and generic properties are distinguished. Attributed properties, which dominate research, assign functions and patterns of behaviour to an organization. In contrast, generic properties refer to the constitutive elements of organizations that take effect before attributed properties. This article takes a closer look at four generic properties by examining their often-implicit use in current political science and public administration research. The aim is to demonstrate that the formal dimension, the goals, the expertise of personnel and organizational boundaries exert an independent influence on the output of political or public sector organizations.
Keywords: 340